PENGGUNAAN DIGITAL AUDIO WORKSTATION (DAW) CUBASE PADA MATA PELAJARAN MUSIK TEKNOLOGI DI KELAS XI MUSIK POPULER SMK NEGERI 7 PADANG - Abdillah Dwi Ravins; Hengki Armez Hidayat (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to determine how the use of the Digital Audio Workstation (DAW) Cubase is implemented in technology music lessons in the XI Popular Music class at SMK Negeri 7 Padang. This study is qualitative research with a descriptive method. The research instruments are the researcher themselves, assisted by writing tools and a camera. Data were collected through observation, interviews, and documentation. The steps for analysing the data are data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that the implementation of technology music learning in the XI Popular Music class at SMK Negeri 7 Padang is conducted in a structured and gradual manner. This research observes the learning process of DAW Cubase, with the aim of strengthening students' understanding of music theory and their skills in digital music production. In each session, students are taught various aspects of using Cubase, from opening and saving project files, writing or drawing projects according to instruments, to selecting and editing VST Instruments. The learning activities are not just theoretical, but also involve direct practice that allows students to collaborate on music projects. This creates an interactive and supportive learning environment where students can help each other and reinforce their understanding.